Fluorescence imaging of drug target proteins using chemical probes - Hao Zhu; Itaru Hamachi (Elsevier, 2020)
Fluorescence imaging can provide valuable information on the expression, distribution, and activity of drug target proteins. Chemical probes are useful small-molecule tools for fluorescence imaging with high structural flexibility and biocompatibility. In this review, we briefly introduce two classes of fluorescent probes for the visualization of drug target proteins. Enzymatically activatable probes make use of the specific enzymatic transformations that generally produce a fluorogenic response upon reacting with target enzymes. Alternatively, specific imaging can be conferred with a ligand that drives the probes to target proteins, where the labeling relies on noncovalent binding, covalent inhibition, or traceless labeling by ligand-directed chemistry.